2013
DOI: 10.3762/bjoc.9.162
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent iodine/TEMPO-mediated oxidation in flow systems: a fast and efficient protocol for alcohol oxidation

Abstract: SummaryHypervalent iodine(III)/TEMPO-mediated oxidation of various aliphatic, aromatic and allylic alcohols to their corresponding carbonyl compounds was successfully achieved by using microreactor technology. This method can be used as an alternative for the oxidation of various alcohols achieving excellent yields and selectivities in significantly shortened reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
(15 reference statements)
0
21
0
1
Order By: Relevance
“…Our initial assumption, based on the formation of cyclic product 6 (see Scheme 2), was that the combination of PhI(OPiv) 2 and LiN 3 led to the generation of azido radicals that, upon reaction with enamide 1,w ould lead to intermediate 7.S ubsequent recombination with another azido radical or SET oxidation followed by trapping by an azide anion would account for the formationo fa dduct 5 (Scheme3). In the presence of TEMPO, interception of 7 by an itroxyl free radicalw ould lead to compound 8.B ased on the known reactivity of TEMPO with iodine (III) reagents, [31] an alternative scenario can be envisaged. [32] In this case, the TEMPO radicalw ould be oxidized to an oxy-ammonium cation, which could be trapped to yield iminium intermediate 9.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial assumption, based on the formation of cyclic product 6 (see Scheme 2), was that the combination of PhI(OPiv) 2 and LiN 3 led to the generation of azido radicals that, upon reaction with enamide 1,w ould lead to intermediate 7.S ubsequent recombination with another azido radical or SET oxidation followed by trapping by an azide anion would account for the formationo fa dduct 5 (Scheme3). In the presence of TEMPO, interception of 7 by an itroxyl free radicalw ould lead to compound 8.B ased on the known reactivity of TEMPO with iodine (III) reagents, [31] an alternative scenario can be envisaged. [32] In this case, the TEMPO radicalw ould be oxidized to an oxy-ammonium cation, which could be trapped to yield iminium intermediate 9.…”
Section: Resultsmentioning
confidence: 99%
“…321 The procedure was applicable for a broad substrate scope. Acid sensitive alcohols (e.g., prenol, The use of hypervalent iodine(III), as terminal oxidant in TEMPO catalyzed oxidations of alcohols in micro flow, has been reported by Wirth et al 322 Kirschning et al reported the use of a functionalized polymer with oxidizing bromate(I) anions in a packed-bed microreactor. 323 The immobilized anions ensured the reactivation of the TEMPO catalyst during the oxidation of a steroid compound to its ketone.…”
Section: Electrochemical Oxidation Processes In Continuous Flowmentioning
confidence: 99%
“…Hypervalent iodine can also be the co-oxidant (328). Perhaps the greenest co-oxidant is the use of electrons as supplied in an electrolytic cell (329).…”
Section: Tempo Oxidationsmentioning
confidence: 99%
“…Hypervalent iodine can be used as the oxidant in TEMPO mediated oxidations of alcohols (see TEMPO section) (328). It can also be used to bring about cyclizations (Scheme 66).…”
Section: Hypervalent Iodine Compoundsmentioning
confidence: 99%